Spate irrigation and poverty in Ethiopia - Hagos, Fitsum; Erkossa, Teklu; Lefore, Nicole; Langan, Simon J. (2014)
The study examined whether the use of spate irrigation in drought-prone areas of Ethiopia reduced poverty. Each of about 25 users of indigenous and modern spate irrigation schemes and an equal number of corresponding nonusers from the same peasant associations in Oromia and Tigray regional states were interviewed. The survey found that the poverty level of the spate irrigation users was significantly lower than that of the nonusers in terms incidence, depth and severity. Access to improved spate irrigation has led to reduced poverty, measured by all poverty indices, compared to traditional spate. Finally, the dominance test showed that the poverty comparison between users and nonusers was robust. From the study, it can be concluded that the use of spate irrigation in areas where access to other alternative water sources is limited, either by physical availability or by economic constraints, can significantly contribute to poverty reduction, and that modernizing the spate system strengthens the impact.